PEMANFAATAN SOSIAL MEDIA SEBAGAI PORTAL LOGIN HOTSPOT PADA UNISBANK (Information Technology and Telematics, 2015)
AbstractOne  technology that continues to grow in the present age is the internet. It is undeniable that today the Internet is part of the basic human needs. Ease  of  access  to  the  Internet  through  a  variety  of media  and  devices  made  access  to  virtual  world easily  and  quickly,  and  some  of  them  comes  with free internet access service.And  in  certain  places  are  also  available free  internet  access  services  using  Hotspot-based WiFi  (Wireless  Fidelity).  WiFi  is  a  wireless-lan technology (WLAN) that only available at one smalllocation  only,  not  like  GPRS,  EDGE,  3G,  HSDPA and  LTE  which  can  reach  up  to  1  city  districts. Hotspot  term  taken  from  the  explanation,  which  is the  hot  spot  at  the  center  /  location  where  WiFi  is located.In  the  implementation  of  WiFi-based Hotspot  with  captive  portal,  certainly  not  everyone will be able to use the facility, as in Unisbank that requires  user  and  password  that  have  been registered previously in the system. Solution to that problem  is  using  login  system  using  Social  Media accounts for the public use, in addition to the ease of use also can be used as a means of promotion.Keywords:  Hotspot,  Mikrotik,  Social  Media, Facebook, Twitter.